THE RELATION OF WATER CHEMICAL QUALITY TO CORAL REEF ECOCSYSTEMS IN DAMAS - Andik Isdianto; Oktiyas Muzaky Luthfi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2020)
Indonesia is an archipelago country that is ranked top of the world for its breadth and wealth. More than 75,000 km2 or almost 14% of the world's coral is in Indonesia. The growth of coral reefs in a sea water is strongly influenced by the quality of waters such as chemical oceanographic factors, namely salinity, pH, DO, nitrate and phosphate. The data collection was carried out twice in September and November 2019 in Damas Waters, Trenggalek, East Java. The purpose of this study is to influence the quality of waters on the growth of coral reefs in Damas, Trenggalek, East Java. The sampling method is purposive random sampling that is the determination of the sample with certain considerations. The location points used by 20 stations are spread, namely on artificial reefs, natural coral reefs, open seas and the area around the harbor. Measurements made include in situ water quality with a multiparameter measurement tool, namely AAQ. The results showed the quality of waters in accordance with environmental quality standards with a value of (1) salinity 31.5 - 3.6 (2) pH 7.9 - 8.1 (3) DO> 5 mg / L (4) Nitrate 0.001-0.007 mg / l (5) Phosphate 0.012 - 0.345 mg / L. Correlation value of all components> 0.5 then the relationship of each parameter and coral reef affect each other.